A tandem Mannich addition–palladium catalyzed ring-closing route toward 4-substituted-3(2H)-furanones - John, Jubi; Târcoveanu, Eliza; Jones, Peter G.; Hopf, Henning (Beilstein Journal of Organic Chemistry, 2014)
A facile route towards highly functionalized 3(2H)-furanones via a sequential Mannich addition–palladium catalyzed ring closing has been elaborated. The reaction of 4-chloroacetoacetate esters with imines derived from aliphatic and aromatic aldehydes under palladium catalysis afforded 4-substituted furanones in good to excellent yields. 4-Hydrazino-3(2H)-furanones could also be synthesized from diazo esters in excellent yields by utilising the developed strategy. We could also efficiently transform the substituted furanones to aza-prostaglandin analogues.
Keywords: aza-prostaglandin analogue; 3(2H)-furanone; Mannich addition; palladium catalysis; tandem reaction